"They are interrelated, one feeds off the other": A taxonomy of perceived disease interactions derived from patients with multiple chronic conditions. Issue 5 (May 2020) - Zulman, Donna M.; Slightam, Cindie A.; Brandt, Kirsten; Lewis, Eleanor T.; Asch, Steven M.; Shaw, Jonathan G.
Highlights: This study presents a taxonomy of patients perceived condition interactions. Patients vary in their experiences with interrelated symptoms and treatments. Acknowledging these perspectives can facilitate shared decision-making. Abstract: Objective: To understand patients' experiences with condition interactions and develop a taxonomy to inform care for patients with multiple chronic conditions. Methods: We conducted qualitative and quantitative analysis of free-text data from patient surveys in which respondents were asked to indicate their most bothersome chronic condition and describe how their other conditions affect their self-care for that condition. Using standard content analysis, we developed a taxonomy comprising how patients perceive interactions among their conditions, and examined cross-cutting themes that reflect qualities of these interactions. Results: Among 383 eligible survey respondents, the mean (SD) number of chronic conditions was 4 (2); common conditions included hypertension (60%), chronic pain (49%), arthritis (41%), depression (32%), diabetes (29%), and post-traumatic stress disorder (26%). Patients' perceived condition interactions took four broad forms: 1) unidirectional interactions among conditions and/or treatments, 2) cyclical or multidimensional interactions, 3) uncertain or indistinct interactions, and 4) no perceived interaction. Cross-cutting themes included beliefs about causal relationships between conditions, identification of interactions as negative vs. positive, and interactions between physical and mental health. Conclusion: This study presents a novel taxonomy of condition interactions from the patient perspective. Practice Implications: Understanding perceived condition interactions may support patient self-management and shared decision-making efforts.